Relationship between organizational culture and performance among German multinational companies in Mexico (Journal of Business, Universidad del Pacífico (Lima, Peru), 2018)
The objective of this research is to determine if there is a relationship between organizational culture and organizational performance in German multinational companies operating in Mexico. To this end, we use a multiple case study, analyzing five German multinational autoparts companies with operations in Mexico, applying a questionnaire to executives at each of the five companies and to 232 employees at one of them. Our main finding is that there is a significant relationship between organizational culture variables and organizational performance variables, such as turnover, job satisfaction, satisfaction with the company, and sales. The study illustrates the importance of promoting human resources policies aimed at increasing employee satisfaction, and studies should be carried out to identify the triggers of satisfaction with greater precision, which may improve the performance of this type of company. The main limitation of this work is that as a case study, the results cannot be generalized;  however, very few previous studies have attempted to establish the relationship between culture and performance in the Mexican context, so this study constitutes a milestone for knowledge in this area.
Keywords: culture; performance; multinationals; social and cultural values